2009
DOI: 10.2139/ssrn.1488376
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Beliefs

Abstract: This paper presents a general framework for studying diverse beliefs in dynamic economies. Within this general framework, the characterization of a central-planner general equilbrium turns out to be very easy to derive, and leads to a range of interesting applications. We show how for an economy with log investors holding diverse beliefs, rational overconfidence is to be expected; volume-of-trade effects are effectively modelled; the Keynesian 'beauty contest' can be modelled and analysed; and bubbles and cras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 49 publications
0
30
0
Order By: Relevance
“…
This note will extend the research presented in Brown & Rogers (2009) to the case of CRRA agents. We consider the model outlined in that paper in which agents had diverse beliefs about the dividends produced by a risky asset.
…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…
This note will extend the research presented in Brown & Rogers (2009) to the case of CRRA agents. We consider the model outlined in that paper in which agents had diverse beliefs about the dividends produced by a risky asset.
…”
mentioning
confidence: 58%
“…Remarks If all the agents have the same discount factor and the agents have logarithmic utility, then Brown & Rogers (2009) showed that the price-dividend ratio was simply ρ −1 1 . In particular, this implied that the volatility of the stock was the same as the volatility of the dividend process.…”
Section: The Stock Pricementioning
confidence: 99%
“…We will now describe our model in detail. As in Brown & Rogers (2009a), we assume that there is unit supply of a single risky asset. This asset produces a dividend continuously in time.…”
Section: The Modelmentioning
confidence: 99%
“…They each have CARA utility. We can use the optimisation problem to characterise the equilibrium as in Brown & Rogers (2009a). Using market clearing we may then determine the state price density.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation